The Cambridge history of the Vietnam War, Volume II, Escalation and stalemate - Preston, Andrew 1973-; Nguyen, Lien-Hang T. 1974- (Cambridge University Press, 2024)
In great depth, Volume II examines the escalation of the Vietnam War and its development into a violent stalemate, beginning with the overthrow of the Ngô Đình Diệm in 1963 to the aftermath of the 1968 Tết Offensive. This five-year period was, for the most part, the fulcrum of a three-decades-long struggle to determine the future of Vietnam and was marked by rival spirals of escalation generated by the Democratic Republic of Vietnam and the United States. The volume explores the war's military aspects on all sides, the politics of war in the two Vietnams and the United States, and the war's international and transnational dimensions in politics, protest, diplomacy, and economics, while also paying close attention to the agency of historical actors on both sides of the conflict in South Vietnam
Title from publisher's bibliographic system (viewed on 10 Jan 2025)
Keywords: Vietnam War, 1961-1975